The cataloguing of musical sources in Silesia by German musicologists from the University of Wroclaw during the first half of the twentieth century - Drożdżewska, Agnieszka (Interdisciplinary Studies in Musicology, 2018)
The most important task undertaken by German musicologists in Wroclaw during the first half of the twentieth century was to catalogue the musical sources of the whole of Silesia, supervised by the Institute of Music (Seminar of Musicology) at the University of Wroclaw, which arose out of the former Royal Academic Institute of Music, established in 1812. The Institute of Music was the first centre to catalogue local musical sources in Wroclaw and the whole region. The Institute’s library was founded during the secularisation process of 1810, and large collections of musical sources were transferred there from regional Catholic churches and monasteries. Thanks to the efforts of Otto Kinkeldey and his doctoral student Hans Erdmann Guckel, the library’s stock was set in order for the first time at the beginning of twentieth century, with clear, uniform shelf-marks given to individual items. In the late 1920s, complex cataloguing was established by Max Schneider and four of his students, Heribert Ringmann, Fritz Koschinsky, Fritz Feldmann and Josef Wittkowski, who searched for unknown and uncatalogued musical sources in the provinces of Silesia. Cooperation with Berlin’s Central Catalogue led to the preparation of detailed descriptions of sources in the form of index cards, though unfortunately only one copy of each card was made and they are now believed to be lost. More detailed evidence was recently found in Schneider’s papers, including reports and correspondence. This enables us to partially reconstruct the scope of the cataloguing campaign, the localities visited and the repertoire that was found. Some of the collections discovered during that campaign and taken to Wroclaw have survived, giving us the possibility of further research orientated towards reconstructing the picture of musical life in Silesia.